Functionalized polyether and polydicyclopentadiene composite material and preparation method thereof
By introducing functionalized polyether oligomers and dicyclopentadiene monomers and using functionalized groups to improve filler compatibility, the poor impact resistance and filler settlement of polybicyclopentadiene materials in low temperature environments are solved. Problem, high strength, toughness, excellent flame retardancy and antibacterial properties are achieved.
Patent Information
- Application Number
- CN202411409679.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-10
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-10-10
AI Technical Summary
Polybicyclopentadiene materials have poor impact resistance under low temperature environments and poor compatibility with the substrate, resulting in interface dehumidification and settlement problems, limiting their application in the field of engineering materials.
Introduce functionalized polyether oligomers and dicyclopentadiene monomers to improve matrix toughness, and improve the compatibility and dispersion of fillers and matrix through functionalized groups such as cyano groups and ester groups, and use specific catalysts and resistors. The polymerizer is cured.
It significantly improves the toughness, impact resistance, flame retardancy and antibacterial properties of polydicyclopentadiene composite materials, solves the problems of filler settlement and compatibility, and improves the overall performance of the material.
Smart Images

Figure BDA0005077646850000031 
Figure BDA0005077646850000051 
Figure BDA0005077646850000052
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polydicyclopentadiene materials, and specifically relates to a functionalized polyether and polydicyclopentadiene composite material and a preparation method thereof. Background Art
[0002] Polydicyclopentadiene (p-DCPD) has a three-dimensional network structure and is a thermosetting polymer material with the advantages of light weight, low cost and easy availability of raw materials, high strength, low water absorption, acid and alkali resistance, and low dielectric. At the same time, it has a fast curing speed, a short production cycle, and low requirements for molding environmental conditions. It is especially suitable for reaction injection molding to produce complex or thin parts. Currently, p-DCPD is widely used in aerospace, shipbuilding, automotive and other fields.
[0003] However, p-DCPD has a large cross-linking density and a low molecular weight between cross-linking points, which results in a large rigidity of the matrix itself, insufficient toughness, poor impact resistance, and difficulty in using it in low-temperature environments, limiting its further application in the fields of engineering materials and special materials. The main means of solving this problem in current research is to directly use solid fillers for filling. Composite materials such as p-DCPD / carbon fiber, p-DCPD / carbon nanotubes, and p-DCPD / glass fiber have been reported. However, since p-DCPD itself is a completely carbon-hydrogen structure and does not contain groups that can interact with solid fillers, the p-DCPD matrix has poor wettability to the filler and poor compatibility between the two. When subjected to external forces, interfacial dehumidification is very likely to occur at the matrix and interface, resulting in stress concentration points, which in turn cause overall material damage. Therefore, directly using filler filling modification can only improve the performance of p-DCPD to a limited extent, especially the impact resistance. Secondly, a small number of studies have reported the use of polar small molecule modifiers to improve the mechanical properties of DCPD composites. However, since the DCPD monomer has an extremely low viscosity, which is close to that of water, the filler is very easy to settle during the curing process, resulting in poor dispersion uniformity of the filler in the matrix, resulting in more defects, and then causing material damage. Therefore, the use of small molecule modifiers is not ideal for improving performance.
[0004] Based on the above background, it is necessary to develop a new copolymer component that can improve the compatibility between the matrix and the filler while improving the toughness of the p-DCPD matrix and solve the sedimentation problem of the filler during the curing process. Summary of the invention
[0005] In view of the above problems existing in the prior art, the present invention aims to provide a functionalized polyether and utilize the functionalized polyether to in-situ toughen a polydicyclopentadiene composite material. The present invention introduces a polyether oligomer containing a functionalized group, so that it is copolymerized with a dicyclopentadiene (DCPD) monomer, thereby fundamentally improving the toughness and low-temperature performance of the matrix; at the same time, polar functionalized groups such as cyano, ester, and Schiff base groups can improve the compatibility of the filler with the matrix and the dispersibility of the filler in the matrix, so that the DCPD composite material has excellent flame retardancy and antibacterial properties, and the resulting modified polydicyclopentadiene material has higher strength, toughness, and excellent low-temperature performance, and also has excellent flame retardancy and antibacterial properties.
[0006] To achieve the above-mentioned object of the invention, the present invention adopts the following scheme:
[0007] A functionalized polyether in-situ toughened polydicyclopentadiene composite material comprises the following components by mass: 23.5% to 61.5% of dicyclopentadiene, 5.5% to 13.0% of functionalized polyether, 25% to 60% of solid filler, 0.05% to 0.3% of catalyst, 0.1% to 0.5% of inhibitor and 1.0% to 3.3% of antioxidant.
[0008] Furthermore, the solid filler is selected from one or more of graphene, carbon fiber, carbon nanotube, glass fiber, montmorillonite, carbon black or white carbon black, preferably carbon fiber.
[0009] Furthermore, the catalyst comprises one or more of a tungsten-based catalyst or a ruthenium-based carbene catalyst, preferably a ruthenium-based carbene catalyst, such as a second-generation Grubbs catalyst.
[0010] Furthermore, the polymerization inhibitor includes one or more of phosphite or phosphate compounds.
[0011] Furthermore, the antioxidant includes one or more of antioxidant 1010 or antioxidant 4010.
[0012] Furthermore, the functionalized polyether is a functionalized polyether with a norbornene structure as the terminal group, and is prepared from an acid anhydride containing a norbornene group and a polyether amine.
[0013] Specifically, the functionalized polyether can be prepared by using existing technologies, such as the preparation method described in CN116535621A.
[0014] Specifically, in a preferred embodiment, the present invention provides a method for preparing a functionalized polyether, comprising the following steps:
[0015] (1) preparing an organic solution of an acid anhydride containing a norbornene group, adding polyetheramine and triethylamine to react overnight at a reaction temperature of 25° C. to 100° C.;
[0016] (2) After the reaction is completed, the obtained solution is distilled under reduced pressure to obtain a yellow viscous liquid, which is a functionalized polyether with a norbornene structure as the terminal group.
[0017] Furthermore, the solvent of the organic solution in step (1) is dichloromethane;
[0018] Furthermore, the acid anhydride containing norbornene groups in step (1) is such as norbornene diacid anhydride;
[0019] Furthermore, in step (1), the molar ratio of the acid anhydride containing norbornene groups, the polyetheramine and the triethylamine is (0.03-0.06):0.03:(0.02-0.05).
[0020] Furthermore, the polyetheramine described in step (1) is selected from one or more of a polyetheramine containing a Schiff base, a chlorine-containing polyetheramine, a cyano-containing polyetheramine and an ester-containing polyetheramine, and specifically may be one or more of the following polymers but not limited to the following, and the molecular weight of the polyetheramine is preferably 200 g / mol to 2000 g / mol.
[0021]
[0022] Furthermore, the polyetheramines listed above can be prepared by referring to the preparation method described in CN117327212A, or commercially available raw materials can be used.
[0023] Furthermore, the reduced pressure distillation in step (2) can be carried out under the conditions of the prior art. In a specific embodiment, reduced pressure distillation at 70-100° C. for 1-5 h can be adopted.
[0024] Another aspect of the present invention provides a method for preparing a functionalized polyether in-situ toughened polydicyclopentadiene composite material, the preparation method comprising the following steps:
[0025] (1) uniformly mixing dicyclopentadiene monomer, functionalized polyether, polymerization inhibitor and antioxidant;
[0026] (2) adding a solid filler to the system obtained in step (1) and mixing uniformly;
[0027] (3) preparing a catalyst solution, adding the catalyst solution to the system obtained in step (2) and mixing uniformly;
[0028] (4) degassing the mixed system obtained in step (3) and pouring it into a mold, heating and curing it to obtain a functionalized polyether in-situ toughened polydicyclopentadiene composite material;
[0029] Further, the concentration of the catalyst solution in step (3) is 50-200 g / L, and the solvent used can be selected from toluene, cyclohexane, etc.;
[0030] Furthermore, the present invention does not limit the heating and curing in step (4), as long as the curing effect is achieved. In a specific embodiment, for example, pre-curing can be performed at 35-50°C for 1-3 hours, and then curing can be performed at 80-100°C for 3-12 hours.
[0031] The beneficial effects of the present invention are:
[0032] (1) The polyether structure has excellent flexibility and low-temperature performance. The present invention is the first to use the method of directly copolymerizing the oligomer with the DCPD monomer to introduce the polyether structure into the p-DCPD matrix, which fundamentally improves the toughness, impact resistance and low-temperature performance of the p-DCPD matrix;
[0033] (2) Functionalized polyether is a kind of oligomer, and its viscosity increases with the increase of molecular weight. It solves the problem that the viscosity of pure DCPD monomer is low and the solid filler is very easy to settle during the curing process, so that the dispersion of the filler in the matrix is effectively improved, and the mechanical properties of the composite material are further improved;
[0034] (3) The introduction of functional groups improves the compatibility and interfacial interaction between the matrix and the solid filler, greatly improving the mechanical properties of the p-DCPD composite material; at the same time, the introduction of functional groups gives the composite material good flame retardancy and antibacterial properties. DETAILED DESCRIPTION
[0035] In order to better understand the technical solution of the present invention, the content of the present invention is further described below in conjunction with the following specific embodiments, but the content of the present invention is not limited to the following embodiments.
[0036] The sources of the main raw materials in the examples and comparative examples of the present invention are as follows; others were obtained from common commercial channels unless otherwise specified.
[0037] Polyetheramine: customized by Beijing Inokai Technology Co., Ltd.
[0038] Toluene: Beijing Inokai Technology Co., Ltd.
[0039] Dicyclopentadiene: Beijing Inokai Technology Co., Ltd.;
[0040] Nadic anhydride: Beijing Inokai Technology Co., Ltd.;
[0041] Triethylamine: Beijing Inokai Technology Co., Ltd.;
[0042] Dichloromethane: Beijing Inokai Technology Co., Ltd.;
[0043] Chopped carbon fiber: Sigma-Aldrich (Shanghai) Trading Co., Ltd.
[0044] Carbon nanotubes: Sigma-Aldrich (Shanghai) Trading Co., Ltd.;
[0045] Glass fiber: Sigma-Aldrich (Shanghai) Trading Co., Ltd.;
[0046] Second-generation Grubbs catalyst: Sigma-Aldrich (Shanghai) Trading Co., Ltd.;
[0047] In each embodiment and comparative example of the present invention, the performance test parameters and corresponding test methods are as follows:
[0048] Tensile strength: Adopt national standard GB / T 1040.2-2006 "Determination of tensile properties of plastics";
[0049] Elongation at break: Adopt national standard GB / T 1040.2-2006 "Determination of tensile properties of plastics";
[0050] Impact strength: using ASTM D6110-2010 standard;
[0051] Limiting oxygen index: adopt the national standard GB / T 2406.1-2008 "Test method for combustion performance of plastics";
[0052] Viscosity: Adopt the national standard GB / T 1632-1993 "Determination of viscosity and intrinsic viscosity of dilute polymer solutions";
[0053] Aging test: The national standard GB / T 3512-2014 "Hot air accelerated aging and heat resistance test for vulcanized rubber and thermoplastic rubber" was used to determine the anti-aging performance, specifically accelerated aging at 120°C for 15 days.
[0054] Example 1
[0055] The structure of a polyetheramine oligomer containing a Schiff base is as follows, and the molecular weight is 600 g / mol.
[0056]
[0057] Take 0.05 mol of anhydride containing norbornene groups, add 150 mL of dichloromethane solution, and stir at room temperature until completely dissolved; then add 0.025 mol of the above Schiff base polyetheramine oligomer and 0.03 mol of triethylamine, and react at room temperature overnight; distill the obtained solution under reduced pressure to obtain functionalized polyether A, whose structure is shown below:
[0058]
[0059] The formula of the functionalized polyether in-situ toughened polydicyclopentadiene composite material is shown in the following table, where the mass fractions are shown.
[0060] Components Comparative Example 1 Recipe I Recipe Ⅱ Formula III DCPD / % 65 59.5 59 56 Functionalized A polyether / % 0 5.5 6 9 Chopped carbon fiber / % 32 32 32 32 Second generation Grubbs catalyst / % 0.2 0.2 0.2 0.2 Inhibitor TPP / % 0.5 0.5 0.5 0.5 Antioxidant 1010 / % 2.3 2.3 2.3 2.3
[0061] According to the formula composition, the functionalized polyether in-situ toughened polydicyclopentadiene composite material is prepared by the following method:
[0062] (1) heating the dicyclopentadiene monomer to 35° C. to melt the monomer, and uniformly mixing the monomer with the functionalized polyether, the polymerization inhibitor, and the antioxidant;
[0063] (2) adding solid filler carbon fiber to the system obtained in step (1) and ultrasonically dispersing for 1 h;
[0064] (3) dissolving the catalyst in toluene at a concentration of 100 g / L, adding the dissolved catalyst solution to the system obtained in step (2) and mixing evenly;
[0065] (4) Degas the mixed system obtained in step (3) and pour it into a mold, heat it to 35° C., and pre-cure it for 2 hours; then heat it to 80° C. and post-cure it for 6 hours.
[0066] The performance test results are shown in the following table:
[0067]
[0068]
[0069] Example 2
[0070] A Cl-containing polyetheramine oligomer has the following structure and a molecular weight of 900 g / mol.
[0071]
[0072] The method for preparing the functionalized polyether is the same as that in Example 1, and a functionalized polyether B is obtained, the structure of which is shown below:
[0073]
[0074] The formula of the Cl-functionalized polyether-modified polydicyclopentadiene composite material is as follows, where the mass fraction is shown:
[0075]
[0076] The functionalized polyether in-situ toughened polydicyclopentadiene composite material was prepared in the same manner as in Example 1, and the performance test results are shown in the following table.
[0077]
[0078]
[0079] Example 3
[0080] A cyano-containing functionalized polyetheramine has the following structure and a molecular weight of 400 g / mol.
[0081]
[0082] The method for preparing the functionalized polyether is the same as that in Example 1, and a functionalized polyether C is obtained, the structure of which is shown below:
[0083]
[0084] The formula of the cyano-functionalized polyether-modified polydicyclopentadiene composite material is as follows, and the mass fraction is shown in the table:
[0085]
[0086] The functionalized polyether in-situ toughened polydicyclopentadiene composite material was prepared in the same manner as in Example 1. The performance test results are shown in the following table:
[0087]
[0088]
[0089] Example 4
[0090] A functionalized polyetheramine containing an ester group has the following structure and a molecular weight of 1100 g / mol.
[0091]
[0092] The method for preparing the functionalized polyether is the same as that in Example 1, and a functionalized polyether D is obtained, and its structure is as follows:
[0093]
[0094] The formula of the functionalized polyether in-situ toughened polydicyclopentadiene composite material is as follows, and the mass fraction is shown in the table:
[0095]
[0096] The functionalized polyether in-situ toughened polydicyclopentadiene composite material was prepared in the same manner as in Example 1. The performance test results are shown in the following table:
[0097]
[0098]
Claims
1. A functionalized polyether in-situ toughened polydicyclopentadiene composite material, characterized in that: The invention comprises the following components by mass: 23.5% to 61.5% of dicyclopentadiene, 5.5% to 13.0% of functionalized polyether, 25% to 60% of solid filler, 0.05% to 0.3% of catalyst, 0.1% to 0.5% of inhibitor and 1.0% to 3.3% of antioxidant; wherein the functionalized polyether is a functionalized polyether with a norbornene structure as the terminal group, and is prepared from an acid anhydride containing a norbornene group and a polyether amine.
2. The functionalized polyether in-situ toughened polydicyclopentadiene composite material according to claim 1, characterized in that: The solid filler includes one or more of graphene, carbon fiber, carbon nanotube, glass fiber, montmorillonite, carbon black or white carbon black, preferably carbon fiber.
3. The functionalized polyether in-situ toughened polydicyclopentadiene composite material according to claim 1, characterized in that: The catalyst comprises one or more of a tungsten-based catalyst or a ruthenium-based carbene catalyst, preferably a ruthenium-based carbene catalyst, and more preferably a second-generation Grubbs catalyst.
4. The functionalized polyether in-situ toughened polydicyclopentadiene composite material according to claim 1, characterized in that: The polymerization inhibitor includes one or more of phosphite or phosphate compounds.
5. The functionalized polyether in-situ toughened polydicyclopentadiene composite material according to claim 1, characterized in that: The antioxidant includes one or more of antioxidant 1010 or antioxidant 4010.
6. A method for preparing a functionalized polyether, characterized in that: Here are the steps: (1) preparing an organic solution of an acid anhydride containing a norbornene group, adding polyetheramine and triethylamine and reacting overnight; (2) After the reaction is completed, the obtained solution is distilled under reduced pressure to obtain a yellow viscous liquid as functionalized polyether.
7. The preparation method according to claim 6, characterized in that: The acid anhydride containing norbornene groups is nadic anhydride; and / or: the solvent of the organic solution is dichloromethane; preferably, the molar ratio of the acid anhydride containing norbornene groups, polyetheramine and triethylamine is (0.03-0.06):0.03:(0.02-0.05).
8. The preparation method according to claim 6 or 7, characterized in that: The polyetheramine is selected from one or more of Schiff base polyetheramine, chlorine-containing polyetheramine, cyano-containing polyetheramine and ester-containing polyetheramine; the polyetheramine is preferably one or more of the following polymers, with a molecular weight of 200 g / mol to 2000 g / mol; 9. A method for preparing a functionalized polyether in-situ toughened polydicyclopentadiene composite material, characterized in that: The following steps are involved: (1) uniformly mixing dicyclopentadiene monomer, functionalized polyether, polymerization inhibitor and antioxidant; (2) adding a solid filler into the mixed system obtained in step (1); (3) preparing a catalyst solution, adding the catalyst solution to the system obtained in step (2) and mixing uniformly; (4) Degassing the mixed system obtained in step (3) and pouring it into a mold, heating and curing it to obtain a functionalized polyether in-situ toughened polydicyclopentadiene composite material.
10. The preparation method according to claim 9, characterized in that: The concentration of the catalyst solution in step (3) is 50-200 g / L, and the solvent used is selected from toluene and cyclohexane; preferably, the heating curing in step (4) is first pre-cured at 35-50° C. for 1-3 h, and then cured at 80-100° C. for 3-12 h.
Citation Information
Patent Citations
Polyimide in-situ reinforced polydicyclopentadiene composite material and preparation method thereof
CN116535621A
Polydicyclopentadiene composite material and preparation method thereof
CN118271577A
Polydicyclopentadiene inorganic complex
KR1020150051787A
Thermally stable polymer-based composite separator for a lithium secondary battery and manufacturing method
US20220384909A1
Heat / Flame-Resistant Polymer Composite-Based Solid Electrolyte Separator, Lithium Secondary Battery, and Manufacturing Method
US20230387548A1